2004
DOI: 10.2214/ajr.182.3.1820657
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Hepatic Tumors: Variability of Lesion Size Using a Single Ablation Device

Abstract: Significant variation occurs in the lesion size produced using the same ablation device and algorithm. These findings must be considered when planning ablation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…The modified automated algorithm [9, 10, 12, 13] begins by activating the impedance control mode with a gradual increase in power output over the first minute to reach 120 W. Power is maintained at this level until tissue impedance rises 20 Ω above the baseline impedance. Once the 20 Ω of threshold is exceeded, the power output is automatically reduced to zero for 15 s. Power is then returned to the initial peak power setting until the tissue impedance rises again.…”
Section: Methodsmentioning
confidence: 99%
“…The modified automated algorithm [9, 10, 12, 13] begins by activating the impedance control mode with a gradual increase in power output over the first minute to reach 120 W. Power is maintained at this level until tissue impedance rises 20 Ω above the baseline impedance. Once the 20 Ω of threshold is exceeded, the power output is automatically reduced to zero for 15 s. Power is then returned to the initial peak power setting until the tissue impedance rises again.…”
Section: Methodsmentioning
confidence: 99%
“…None have focused on a direct comparison of different experimental results in terms of coagulation zone size and the evolution of electrical variables. The task is even harder if clinical results are used, since they can vary immensely, from 1.7 to 5.3 cm [34]. This is possibly due to variations in tissue characteristics and procedural factors, such as multiple applications of RF power on the same target to increase total coagulation zone size by overlapping.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…However, none of these approaches provides the physician performing the procedure with vital information concerning induced lesion size while the patient is still on the operating table. As a recent study (Montgomery et al 2004) has demonstrated that identical ablation equipment and treatment protocols can produce lesions of markedly different sizes in different patients, monitoring the size of the induced thermal lesion during RF ablation procedures is essential to optimize the safety and success of the technique.…”
Section: Introductionmentioning
confidence: 99%